Audiological Tests Used in the Evaluation of the Effects of Solvents on the Human Auditory System: A Mixed Methods Review - Roggia, Simone Mariotti; Zucki, Fernanda; Fuente, Adrian; Lacerda, Adriana Bender Moreira de; Gong, Wei; Carlson, Krystin; Morata, Thais C. (Seminars in Hearing, 2023)
This study aimed to scope the literature, identify knowledge gaps, appraise results, and synthesize the evidence on the audiological evaluation of workers exposed to solvents. We searched Medline, PubMed, Embase, CINAHL, and NIOSHTIC-2 up to March 22, 2021. Using Covidence, two authors independently assessed study eligibility, risk of bias, and extracted data. National Institute of Health Quality Assessment Tools was used in the quality evaluation of included studies; the Downs and Black checklist was used to assess the risk of bias. Of 454 located references, 37 were included. Twenty-five tests were studied: two tests to measure hearing thresholds, one test to measure word recognition in quiet, six electroacoustic procedures, four electrophysiological tests, and twelve behavioral tests to assess auditory processing skills. Two studies used the Amsterdam Inventory for Auditory Disability and Handicap. The quality of individual studies was mostly considered moderate, but the overall quality of evidence was considered low. The discrepancies between studies and differences in the methodologies/outcomes prevent recommending a specific test battery to assess the auditory effects of occupational solvents. Decisions on audiological tests for patients with a history of solvent exposures require the integration of the most current research evidence with clinical expertise and stakeholder perspectives.
Keywords: solvents; ototoxicity; work-related hearing loss; scoping review